Interaction of human, rat, and mouse immunoglobulin A (IgA) with staphylococcal superantigen-like 7 (SSL7) decoy protein and leukocyte IgA receptor - Wines, B.; Ramsland, Paul; Trist, H.; Gardam, S.; Brink, R.; Fraser, J.; Hogarth, P. (2011)
Host survival depends on an effective immune system and pathogen survival on the effectiveness of immune evasion mechanisms. Staphylococcus aureus utilizes a number of molecules to modulate host immunity, including the SSL family of which SSL7 binds IgA and inhibits Fca receptor I (FcaRI)-mediated function. Other Gram-positive bacterial pathogens produce IgA binding proteins, which, similar to SSL7, also bind the Fc at the CH2/CH3 interface (the junction between constant domains 2 and 3 of the heavy chain). The opposing activities of the host FcaRI-IgA receptor ligand pair and the pathogen decoy proteins select for host and pathogen variants, which exert stronger protection or evasion, respectively. Curiously, mouse but not rat IgA contains a putative N-linked glycosylation site in the center of this host receptor and pathogen-binding site. Here, we demonstrate that this site is glycosylated and that the effect of amino acid changes and glycosylation of the CH2/CH3 interface inhibits interaction with the pathogen IgA binding protein SSL7, while maintaining binding of pIgR, essential to the biosynthesis and transport of SIgA. © 2011 by The American Society for Biochemistry and Molecular Biology, Inc.